Locomotives for Operation in Nordic Conditions (Current Problems in Rail Vehicles, 2025)
Since 2022, CZ LOKO, a.s. has entered the Swedish market by delivering a new locomotive from the 744.1 / Effishunter 1000 product line. During this time and after new experiences with the specifics of railway operation in Nordic conditions in Sweden, necessary modifications and measures have been made. All modifications in accordance with TSI and national requirements have been tested on a prototype and certified for series production.
Keywords: nordic conditions; Effishunter; winterization